(untitled) (Agricultural Engineering, 2018)
Due to low effectiveness or high costs of using chemical agents in the protection of common mushrooms, producers are forced to look for alternative methods of protection. One such method is the use of preparations containing beneficial microorganisms. A statistical evaluation of this mushroom protection method and determination of the number of infected fruiting bodies is presented in this paper.